Properties of probability productive dependencies in the data analysis of large data volumes - Pshenychnyi, Oleksandr (Publishing House of Lviv Polytechnic National University, 2012)
This paper describes findings in the area of aggregated associative dependencies detection. The work gives a method of building aggregated associative dependencies in large data volumes. This research can be applied to the wide range of data types and optimize data mining processes. У статті наведено результати дослідження властивостей асоціативних залежностей та можливостей їх ефективного агрегування. Розрозблено метод виявлення асоціативних залежностей широкого класу у великих наборах даних.
Властивості асоціативних залежностей у аналізі даних
Keywords: aggregated associative dependency; data mining; large data volume; functional dependency